(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the particular methodological parameters that influence the effectiveness of teaching English in contemporary educational contexts. The study adopts a mixed-methods approach, combining theoretical analysis with empirical data collected through classroom observations, questionnaires, and language testing. The findings reveal that clearly defined instructional objectives, learner-centered approaches, communicative teaching methods, appropriate material selection, and systematic assessment strategies play a significant role in enhancing learners’ language skills and communicative competence.